The economics of the Internet of Things in the Global South. - Kshetri, Nir (Third World Quarterly, 2017)
While the Internet of Things (IoT) is not new, its key components are becoming increasingly affordable now, which makes the technology extremely attractive for the Global South. By collecting data from various IoT sources, combining them with data from other sources and using big data analytics, decisions can be made and actions can be taken that can have important economic, social, ecological and environmental implications in these countries. The most visible impacts of the IoT in these countries include improvements in agricultural and food systems, enhancement of environmental security and resource conservation, achievement of better healthcare, public health and medicine, and enhancement of the efficiency of key industries. This paper provides an overview of how the IoT is currently being used in the Global South. It also discusses the opportunities and challenges that IoT initiatives present there. The analysis indicates that the IoT may address some of the institutional bottlenecks, technological challenges and key sources of high transaction costs. On the other hand, various sources of underdevelopment may act as barriers to full utilisation of the IoT.